(untitled) (Veterinary Science, 2025)
The aim of this study was to describe the etiology and abundance of goat and sheep gastrointestinal nematodes (GIN) in different ecological regions of Northwest of Argentina (ANW). GIN was recovered from samples collected from necropsies carried out for different diagnostic cases (n= 117) from the following regions: chaqueña semi-arid, temperate valleys and humid forest, arid canyon and valleys and Puna of the provinces of Salta, Jujuy and Santiago del Estero. From abomasum and intestines samples GIN were recovered and counted. GIN species count differences were processed by non-parametric variance analysis and chi square. Recovered NGI and their respective prevalences were Haemonchus contortus (98,3%), Teladorsagia circumcincta (53,0%), Trichostrongylus axei (38,5%) Trichostrongylus colubriformis (85,5%), Trichuris spp. (41,9%), Oesophagostomum spp. (17,1%), Nematodirus spathiger (13,7%), Strongyloides papillosus (5,5%) and Cooperia curticei (1,1%). Burdens of H. contortus, T. colubriformis and total NGI recovered from the temperate valleys and humid forest ecoregions were higher (p<0.0001) than those recovered in the rest of the ecoregions. H. contortus, T. colubriformis and total NGI burdens recovered during summer and autumn were higher (p<0.0001) than those recovered from animals necropsied in winter and spring. It is concluded that H. contortus and T. colubriformis are the species of greatest productive importance for goats and sheep in ANW, with the temperate valleys and humid forest and summer-autumn period being the most favorable for NGI involving a greater risk of productive losses